2019
DOI: 10.1063/1.5088790
|View full text |Cite
|
Sign up to set email alerts
|

Structural, magnetic, and electrical properties of collinear antiferromagnetic heteroepitaxy cubic Mn3Ga thin films

Abstract: Although a cubic phase of Mn3Ga with an antiferromagnetic order has been theoretically predicted, it has not been experimentally verified in a bulk or film form. Here, we report the structural, magnetic, and electrical properties of antiferromagnetic cubic Mn3Ga (C-Mn3Ga) thin films, in comparison with ferrimagnetic tetragonal Mn3Ga (T-Mn3Ga). The structural analyses reveal that C-Mn3Ga is heteroepitaxially grown on MgO substrate with the Cu3Au-type cubic structure, which transforms to T-Mn3Ga as the RF sputte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…PLEASE CITE THIS ARTICLE AS DOI: 10.1063/5.0001349 evaluate the Curie temperature (TC) of the films. The curve shows a monotonically decreasing magnetization with increasing temperature, and the TC is higher than 400 K.Ref 15. reported TC = 800 K for tetragonal Mn3Ga.In summary, we have grown epitaxial Mn2.6Ga thin films on MgO(001)substrates with different thicknesses.…”
mentioning
confidence: 84%
See 4 more Smart Citations
“…PLEASE CITE THIS ARTICLE AS DOI: 10.1063/5.0001349 evaluate the Curie temperature (TC) of the films. The curve shows a monotonically decreasing magnetization with increasing temperature, and the TC is higher than 400 K.Ref 15. reported TC = 800 K for tetragonal Mn3Ga.In summary, we have grown epitaxial Mn2.6Ga thin films on MgO(001)substrates with different thicknesses.…”
mentioning
confidence: 84%
“…PLEASE CITE THIS ARTICLE AS DOI: 10.1063/5.0001349 deposition rate appears to be important in promoting the epitaxial reorientation, and increasing the deposition rate suppresses the (111) peak in 50 nm thick films. Bang et al 15 also found that the cubic phase was favored at lower growth rates but transitioned to mixed then tetragonal films at higher growth rates and lower Mn content.…”
mentioning
confidence: 94%
See 3 more Smart Citations